Content Marketing Analysis in Building Customer Engagement through Social Media Platforms - ST. Namirah Nur Rahma; Arianto Arianto; Muh Akbar; Sitti Nurfaizah (Jurnal Administrasi Bisnis, 2026)
This study seeks to examine the function of content marketing in fostering consumer interaction via social media platforms, specifically Instagram, within service-oriented enterprises. The growing utilization of digital platforms has transformed marketing strategies from conventional methods to more interactive and content-centric communication, necessitating an understanding of how content affects audience engagement. This study employs a qualitative descriptive methodology. Data were gathered via the monitoring of social media material, comprehensive interviews with content managers and users, and documentation analysis. The data were examined utilizing an interactive model that encompassed data reduction, data visualization, and conclusion formulation to discern patterns in content strategy and audience engagement. The results demonstrate that content marketing significantly enhances client engagement. Diverse content kinds, such as promotional, educational, informational, and testimonial, yield varying effects on audience engagement. Visual and interactive content, enhanced by platform functionalities like tales, reels, and direct messaging, is particularly successful in augmenting engagement levels and reinforcing brand perception. This study indicates that consistency, inventiveness, and content relevance are critical characteristics affecting successful engagement techniques, despite constraints regarding scope and generalizability. This study's distinctiveness resides in its complete examination of content marketing techniques within a broader framework, delivering practical insights for organizations